Preparation method of lithium ion battery and lithium ion battery
The thermal polymerization of electrolytes of lithium-ion batteries is solved by the two-step heating method, and the problems of side reactions and aging and cracking at high temperatures in traditional methods are significantly improved.
Patent Information
- Application Number
- CN202411818618.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-25
AI Technical Summary
The traditional in-situ polymerization method performs long-term high-temperature polymerization at high temperatures, which can easily lead to side reactions and aging and cracking of polymers, resulting in deterioration of lithium-ion battery performance.
The electrolyte thermal polymerization was performed by two-step heating method. The first heating treatment temperature was 70°C-100°C, the time was 1h-12h, and the second heating treatment temperature was 45°C-60°C, the time was 8h-24h. The polymerization reaction was promoted by initiators such as benzoyl peroxide, N,N-dimethylaniline, and tert-butyl benzoate peroxide.
It reduces the side reaction between polymer monomer and electrode and the aging and cracking problems of polymers at high temperatures, and improves the mechanical and electrochemical properties of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a preparation method of a lithium ion battery and a lithium ion battery. Background Art
[0002] With the development of science and technology, lithium-ion batteries with high energy density and long cycle life are being widely used in many consumer electronic products such as smart wearables and mobile communications. Traditional liquid lithium-ion batteries have great safety risks due to the presence of flammable liquid electrolytes; solid polymer electrolytes have the advantages of high mechanical strength, good electrochemical stability, and good thermal stability, which can significantly improve the safety performance of lithium batteries.
[0003] In the related art, the solid polymer electrolyte is formed by an in-situ polymerization method. The electrolyte is injected into the battery cell. Under the action of external conditions and initiators, the polymer monomers in the electrolyte undergo a polymerization reaction, thereby forming a solid polymer electrolyte in situ.
[0004] However, the traditional in-situ polymerization method generally uses long-term high-temperature polymerization at the same temperature. The reactants are at a high temperature for a long time, which makes it easy for side reactions and polymer aging and cracking to occur during the in-situ polymerization reaction, resulting in battery performance degradation. Summary of the invention
[0005] The embodiments of the present invention provide a method for preparing a lithium ion battery and a lithium ion battery, which can improve the technical problem of battery performance degradation caused by long-term high-temperature polymerization at the same temperature in an in-situ polymerization method.
[0006] In a first aspect, an embodiment of the present invention provides a method for preparing a lithium ion battery, the method comprising the following steps:
[0007] A method for preparing a lithium ion battery, the method comprising the following steps:
[0008] Providing an electrolyte, the electrolyte comprising a polymer monomer and an initiator, the initiator comprising at least one of benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate;
[0009] Injecting the electrolyte into a battery cell, performing a first heating treatment on the battery cell to obtain an intermediate, wherein the heating temperature of the first heating treatment is 70° C.-100° C., and the heating time is 1 h-12 h;
[0010] The intermediate is subjected to a second heating treatment to obtain the lithium-ion battery, wherein the heating temperature of the second heating treatment is 45° C.-60° C., and the heating time is 8 h-24 h.
[0011] In one embodiment, the polymer monomer includes at least one of 2-phenoxyethyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, acrylonitrile, 2-cyano-3-ethoxyethyl acrylate, adiponitrile, hexamethylene diisocyanate, and vinyl trimethoxysilane; and / or
[0012] The mass of the polymer monomer accounts for 0.1%-20% of the mass of the electrolyte; and / or
[0013] The mass of the initiator accounts for 0.1%-5% of the mass of the electrolyte.
[0014] In one embodiment, the method for preparing the electrolyte comprises the following steps:
[0015] The polymer monomer, the initiator and other raw materials are mixed in a prescribed amount to obtain the electrolyte.
[0016] In one embodiment, the other raw materials include organic solvents, lithium salts, additives and cross-linking agents; and / or
[0017] The mixing is carried out in dry air, argon atmosphere or nitrogen atmosphere; and / or
[0018] The mixing temperature is 20° C.-30° C., and / or the mixing time is 2 h-24 h.
[0019] In one embodiment, the mass of the cross-linking agent accounts for 0.1%-10% of the mass of the electrolyte; and / or
[0020] The mass of the organic solvent accounts for 70%-88% of the mass of the electrolyte; and / or
[0021] The mass of the lithium salt accounts for 9%-20% of the mass of the electrolyte; and / or
[0022] The mass of the additive accounts for 0.5%-10% of the mass of the electrolyte.
[0023] In one embodiment, the crosslinking agent includes at least one of triethylene glycol dimethacrylate, diallyl disulfide, N,N-methylenebisacrylamide, propoxy neopentyl glycol diacrylate, pentaerythritol tetraacrylate, diallyl isophthalate, divinyl propylene terephthalate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and divinylbenzene; and / or
[0024] The organic solvent comprises at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate and propylene carbonate; and / or
[0025] The lithium salt comprises at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, lithium bisfluorobisoxalate phosphate, lithium difluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bisoxalate borate, and lithium difluorooxalate borate; and / or
[0026] The additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl vinyl carbonate, 1,3-propane sultone, trimethylsilane, vinyl vinyl sulfite, and dimethyl sulfoxide.
[0027] In one embodiment, before the first heating treatment is performed on the battery cell, a packaging step and a standing step are also included.
[0028] In one embodiment, the standing temperature is 20°C-30°C, and / or the standing time is 12h-48h.
[0029] In one embodiment, the packaging includes vacuum packaging, and the vacuum degree of the vacuum packaging is -70 kPa to -90 kPa.
[0030] In a second aspect, an embodiment of the present invention provides a lithium ion battery, wherein the lithium ion battery is prepared by the preparation method described above.
[0031] Beneficial effects of the embodiments of the present invention:
[0032] The invention provides a preparation method of a lithium ion battery and a lithium ion battery. The preparation method adopts a two-step heating method to perform electrolyte thermal polymerization. On the one hand, the initiator in the electrolyte includes at least one of benzoyl peroxide, N,N-dimethylaniline and tert-butyl perbenzoate, and these initiators have high initiation activity. During the first heating treatment, the higher temperature makes the initiation activity of the initiator higher, and most of the polymer monomers in the electrolyte can be reacted to generate solid polymers within a time range of 1h-12h. The first heating treatment time is short, which can reduce the side reactions between the polymer monomers and the electrodes at high temperature, and at the same time, can reduce the generated polymer monomers. On the other hand, after the first heating treatment, the intermediate is subjected to a second heating treatment at a temperature between 45°C and 60°C, which allows the polymerization reaction to continue at a relatively low temperature, thereby reducing the problem of aging and cracking of the generated polymer during the second heating treatment. In addition, initiators such as benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate still have a certain initiation activity at a relatively low temperature, which can promote the polymerization reaction of unreacted polymer monomers during the second heating treatment, thereby further improving the conversion rate of polymer monomers. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.
[0034] In the related art, the in-situ polymerization method generally uses the same temperature for long-term high-temperature polymerization. The reactants are at a relatively high temperature for a long time, which makes it easy for more side reactions and polymer aging and cracking to occur during the in-situ polymerization reaction, resulting in battery performance degradation, which needs further improvement.
[0035] To solve the above problems, the present invention provides a method for preparing a lithium ion battery, the method comprising the following steps:
[0036] S1. Providing an electrolyte, wherein the electrolyte comprises a polymer monomer and an initiator, wherein the initiator comprises at least one of benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate;
[0037] S2, injecting the electrolyte into the battery cell, and performing a first heating treatment on the battery cell to obtain an intermediate, wherein the heating temperature of the first heating treatment is 70° C.-100° C., and the heating time is 1 h-12 h;
[0038] S3, performing a second heating treatment on the intermediate to obtain a lithium-ion battery, wherein the heating temperature of the second heating treatment is 45° C.-60° C., and the heating time is 8 h-24 h.
[0039] In this embodiment, a method for preparing a lithium-ion battery is provided. The method adopts a two-step heating method to perform electrolyte thermal polymerization. On the one hand, the initiator in the electrolyte includes at least one of benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate; during the first heating treatment, the higher temperature makes the initiator more active, and most of the polymer monomers in the electrolyte can react to generate solid polymers within a time range of 1h-12h. The first heating treatment time is short, which can reduce the polymer monomers from reacting with the electrode due to high reaction activity for a long time under high temperature conditions, and at the same time, can reduce the problem of aging and cracking of the generated polymer due to being in a high temperature state for a long time; on the other hand, after the first heating treatment is completed, the obtained intermediate is subjected to a second heating treatment, and the temperature of the second heating treatment is between 45°C and 60°C, which can allow the polymerization reaction to continue at a relatively low temperature, and reduce the problem of aging and cracking of the generated polymer during the second heating treatment. In addition, initiators such as benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate themselves still have certain initiation activity at a relatively low temperature, which can effectively promote the unreacted polymer monomers in the intermediate to continue the polymerization reaction under low temperature conditions, and further improve the conversion rate of the polymer monomers.
[0040] In this embodiment, the heating temperature of the first heating treatment is 70°C-100°C; optionally, the heating temperature of the first heating treatment can be any one of 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc. or a range between any two. In this embodiment, when the temperature of the first heating treatment is higher than 100°C, the excessively high temperature easily causes the initiation activity of initiators such as benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate to be too high, resulting in the polymerization reaction rate of the first heating treatment being too fast and causing implosion. At the same time, the excessively high temperature of the first heating treatment easily accelerates the expansion and cracking of the polymer; when the temperature of the first heating treatment is lower than 70°C, the excessively low temperature easily leads to a slow polymerization reaction rate and a decrease in the conversion rate of the polymer monomers. After the first heating treatment is completed, there are too many residual polymer monomers, and during the second heating treatment, the excessive residual polymer monomers easily cause a decrease in the conversion rate of the polymer monomers and a decrease in the molecular weight of the polymer due to the lower temperature of the second heating treatment, which affects the mechanical properties and electrochemical properties of the battery.
[0041] In the present embodiment, the heating time of the first heat treatment is 1h-12h. Optionally, the heating time of the first heat treatment can be any one of 1h, 3h, 5h, 7h, 9h, 12h, etc. or a range between any two. In the present embodiment, when the time of the first heat treatment is greater than 12h, the excessively long reaction time is likely to cause the residual polymer monomer to have a higher reaction activity due to being at high temperature for a long time, thereby increasing the side reactions between the polymer monomer and the electrode. At the same time, the produced polymer is prone to aging and cracking at high temperature for a long time, affecting the performance of the battery; when the time of the first heat treatment is less than 1h, the excessively short reaction time is likely to cause incomplete polymerization reaction, and after the first heat treatment is completed, there are too many residual polymer monomers in the intermediate.
[0042] In this embodiment, the heating temperature of the second heating treatment is 45°C-60°C. Optionally, the heating temperature of the second heating treatment can be any one of 45°C, 48°C, 50°C, 53°C, 56°C, 58°C, 60°C, etc. or a range between any two. In this embodiment, after the first heating treatment is completed, more solid polymers are produced in the intermediate. The lower reaction temperature in the second heating treatment can reduce the aging and cracking of the existing polymers. At the same time, the small amount of polymer monomers remaining in the intermediate can continue to react in the second heating treatment stage, which can reduce the residual polymer monomers, improve the purity of the product, and reduce the battery impedance.
[0043] In this embodiment, when the temperature of the second heat treatment is higher than 60°C, the excessively high temperature can easily cause the generated polymer to crack, and increase the side reaction between the polymer monomer and the electrode; when the temperature of the second heat treatment is lower than 45°C, the excessively low temperature can easily cause the polymerization reaction rate to slow down and the polymer monomer conversion rate to decrease.
[0044] In this embodiment, the heating time of the second heating treatment is 8h-24h. Optionally, the heating time of the second heating treatment can be any one of 8h, 10h, 13h, 16h, 18h, 20h, 24h, etc. or a range between any two. In this embodiment, when the time of the second heating treatment is greater than 24h, too long a reaction time is likely to lead to reduced production efficiency; when the time of the second heating treatment is less than 8h, too short a reaction time is likely to lead to incomplete polymerization, increased residual amounts of polymer monomers and initiators, and increased battery impedance.
[0045] In one embodiment, the mass of the initiator accounts for 0.1%-5% of the mass of the electrolyte; optionally, the mass fraction of the initiator can be any one of 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, etc. or a range between any two. In this embodiment, when the mass of the initiator is too small, it is easy to cause the polymerization reaction rate to slow down and the polymerization reaction to be incomplete, thereby reducing the conversion rate of the polymer monomer; when the mass of the initiator is too large, it is easy to cause the polymerization reaction rate to be too fast and produce implosion.
[0046] In one embodiment, the polymer monomers include at least one of 2-phenoxyethyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, acrylonitrile, 2-cyano-3-ethoxyethyl acrylate, adiponitrile, hexamethylene diisocyanate, and vinyl trimethoxysilane. In this embodiment, initiators such as benzoyl peroxide, N,N-dimethylaniline, and tert-butyl peroxybenzoate can effectively initiate polymerization of these polymer monomers.
[0047] In one embodiment, the mass of the polymer monomer accounts for 0.1%-20% of the mass of the electrolyte; optionally, the mass fraction of the polymer monomer can be any one of 0.1%, 1%, 3%, 6%, 10%, 13%, 16%, 18%, 20%, etc. or a range between any two. In this embodiment, when the mass of the polymer monomer is too much, it is easy to cause the polymer molecular weight to be too high and the mechanical strength to be too large; when the mass of the polymer monomer is too little, it is easy to cause the polymer molecular weight to be too low, affecting the mechanical properties and electrochemical properties of the battery.
[0048] In one embodiment, before the first heating treatment is performed on the battery cell, the following step is further included: encapsulating the battery cell body. In this embodiment, encapsulating the battery cell can reduce the impact of the external environment on the battery cell, and at the same time, reduce the leakage and volatilization of the electrolyte inside the battery cell.
[0049] In one embodiment, the packaging includes vacuum packaging, and the vacuum degree of the vacuum packaging is -70 kPa to -90 kPa. Optionally, the vacuum degree of the vacuum packaging is any one of -70 kPa, -74 kPa, -78 kPa, -80 kPa, -84 kPa, -87 kPa, -90 kPa, etc., or a range between any two thereof.
[0050] In one embodiment, before the first heating treatment is performed on the battery cell, the following step is further included: the battery cell body is subjected to a static treatment. In this embodiment, the static treatment of the battery cell allows the electrolyte to be fully diffused inside the battery cell, so that each part inside the battery cell can be evenly infiltrated by the electrolyte.
[0051] In one embodiment, the standing temperature is 20°C-30°C, and the standing time is 12h-48h. Optionally, the standing temperature can be any one of 20°C, 22°C, 25°C, 27°C, 29°C, 30°C, etc., or a range between any two thereof; the standing time can be any one of 12h, 15h, 20h, 25h, 30h, 35h, 40h, 44h, 48h, etc., or a range between any two thereof.
[0052] In one embodiment, the method for preparing the electrolyte includes the following steps: mixing the polymer monomer, initiator and other raw materials in the formulated amounts to obtain the electrolyte.
[0053] In one embodiment, the mixing step can be performed in dry air, argon atmosphere, or nitrogen atmosphere, which is not limited herein.
[0054] In one embodiment, the mixing temperature is 20°C-30°C, and / or the mixing time is 2h-24h. Optionally, the mixing temperature can be any one of 20°C, 22°C, 25°C, 27°C, 29°C, 30°C, etc., or a range between any two thereof; the mixing time can be any one of 2h, 5h, 8h, 10h, 14h, 18h, 20h, 22h, 24h, etc., or a range between any two thereof.
[0055] In one embodiment, other raw materials further include an organic solvent, a lithium salt, an additive and a cross-linking agent.
[0056] In one embodiment, the organic solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, and propylene carbonate.
[0057] In one embodiment, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, lithium bisfluorobisoxalate phosphate, lithium difluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bisoxalate borate, and lithium difluorooxalate borate.
[0058] In one embodiment, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl vinyl carbonate, 1,3-propane sultone, trimethylsilane, vinyl vinyl sulfite, and dimethyl sulfoxide.
[0059] In one embodiment, the crosslinking agent includes at least one of triethylene glycol dimethacrylate, diallyl disulfide, N,N-methylenebisacrylamide, propoxy neopentyl glycol diacrylate, pentaerythritol tetraacrylate, diallyl isophthalate, divinyl propylene terephthalate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and divinylbenzene.
[0060] In one embodiment, the mass of the organic solvent accounts for 70%-88% of the mass of the electrolyte; optionally, the mass fraction of the organic solvent can be any one of 70%, 75%, 78%, 80%, 83%, 86%, 88%, etc. or a range between any two.
[0061] In one embodiment, the mass of the lithium salt accounts for 9%-20% of the mass of the electrolyte; optionally, the mass fraction of the lithium salt can be any one of 9%, 13%, 16%, 18%, 20%, etc. or a range between any two.
[0062] In one embodiment, the mass of the additive accounts for 0.5%-10% of the mass of the electrolyte. Optionally, the mass fraction of the additive can be any one of 0.5%, 1%, 3%, 5%, 7%, 9%, 10%, etc. or a range between any two.
[0063] In one embodiment, the mass of the cross-linking agent accounts for 0.1%-10% of the mass of the electrolyte; optionally, the mass fraction of the cross-linking agent can be any one of 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 5%, 7%, 9%, 10%, etc., or a range between any two.
[0064] The present application also provides a lithium-ion battery, wherein the lithium-ion battery is prepared by the above method. In this embodiment, the electrolyte of the lithium-ion battery is not easy to age and crack, and the residual polymer monomer and side reactions in the lithium-ion battery are small, which can effectively improve the mechanical properties and electrochemical properties of the lithium-ion battery.
[0065] In this embodiment, the type of lithium-ion battery is not limited, and the lithium-ion battery can be one of a ternary soft-pack battery, a ternary steel-shell battery, a lithium cobalt oxide soft-pack battery, and a lithium cobalt oxide steel-shell battery.
[0066] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present application are described in detail as follows:
[0067] Example 1
[0068] This embodiment provides a method for preparing a lithium ion battery, comprising the following steps:
[0069] (1) under an argon atmosphere, mixing an organic solvent, a lithium salt, an additive, an initiator, a cross-linking agent and a polymer monomer at 25° C. to obtain an electrolyte;
[0070] Wherein, the lithium salt is lithium hexafluorophosphate, and the mass percentage of the lithium salt in the electrolyte is 10%;
[0071] The organic solvent is composed of ethylene carbonate and ethyl methyl carbonate, and the mass percentage of the organic solvent in the electrolyte is 73%;
[0072] The additive is vinylene carbonate, and the mass percentage of the additive in the electrolyte is 0.5%;
[0073] The initiator is benzoyl peroxide, and the mass percentage of the initiator in the electrolyte is 0.6%;
[0074] The cross-linking agent is triethylene glycol dimethacrylate, and the mass percentage of the cross-linking agent in the electrolyte is 5%;
[0075] The polymer monomer is pentaerythritol tetraacrylate, and the mass percentage of the polymer monomer in the electrolyte is 10.9%.
[0076] (2) The negative electrode material graphite, the conductive agent acetylene black and the binder sodium carboxymethyl cellulose and styrene-butadiene rubber were prepared into a slurry in a mass percentage of 94:1:2:3, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet; the positive electrode material NCM811 (Li Ni 0.8 Co 0.1 Mn 0.1 O2), conductive agent acetylene black and binder polyvinylidene fluoride are prepared into a slurry in a mass ratio of 95:3:2, coated on an aluminum foil current collector, and dried to obtain a positive electrode sheet; the positive electrode sheet, negative electrode sheet and separator are assembled to obtain a battery cell.
[0077] (3) Injecting electrolyte into the battery cell, vacuum packaging, and allowing to stand; wherein the vacuum degree of the vacuum packaging is -80 kPa, the temperature of the standing is 25° C., and the standing time is 24 hours.
[0078] (4) placing the rested battery cell into an oven for a first heating treatment to obtain an intermediate; wherein the heating temperature is 85° C. and the heating time is 6 hours.
[0079] (5) placing the intermediate in an oven for a second heating treatment to obtain a lithium-ion battery; wherein the heating temperature is 50° C. and the heating time is 16 h.
[0080] Example 2
[0081] The difference between Example 2 and Example 1 is:
[0082] In step (4), the heating temperature of the first heat treatment is 70°C, and the rest is the same as in Example 1.
[0083] Example 3
[0084] The difference between Example 3 and Example 1 is:
[0085] In step (4), the heating temperature of the first heat treatment is 100° C., and the rest is the same as in Example 1.
[0086] Example 4
[0087] The difference between Example 4 and Example 1 is:
[0088] In step (4), the heating time of the first heating treatment is 1 hour, and the rest is the same as in Example 1.
[0089] Example 5
[0090] The difference between Example 5 and Example 1 is:
[0091] In step (4), the heating time of the first heating treatment is 12 hours, and the rest is the same as in Example 1.
[0092] Example 6
[0093] The difference between Example 6 and Example 1 is:
[0094] In step (5), the heating temperature of the second heat treatment is 45°C, and the rest is the same as in Example 1.
[0095] Example 7
[0096] The difference between Example 7 and Example 1 is:
[0097] In step (5), the heating temperature of the second heat treatment is 60°C, and the rest is the same as in Example 1.
[0098] Example 8
[0099] The difference between Example 8 and Example 1 is:
[0100] In step (5), the heating time of the second heating treatment is 8 hours, and the rest is the same as in Example 1.
[0101] Example 9
[0102] The difference between Example 9 and Example 1 is:
[0103] In step (5), the heating time of the second heating treatment is 24 hours, and the rest is the same as in Example 1.
[0104] Example 10
[0105] The difference between Example 10 and Example 1 is that:
[0106] In step (1), the initiator is N,N-dimethylaniline, and the rest is the same as in Example 1.
[0107] Embodiment 11
[0108] The difference between Example 11 and Example 1 is that:
[0109] In step (1), the initiator is tert-butyl perbenzoate, and the rest is the same as in Example 1.
[0110] Comparative Example 1
[0111] The difference between Comparative Example 1 and Example 1 is:
[0112] The operation of step (4) is not performed;
[0113] The corresponding change of step (5) is: placing the battery cell after standing still into an oven for heating treatment to obtain a lithium-ion battery; wherein the heating temperature is 50° C. and the heating time is 16 hours.
[0114] Comparative Example 2
[0115] The difference between Comparative Example 2 and Example 1 is:
[0116] Step (5) was not performed.
[0117] Comparative Example 3
[0118] The difference between Comparative Example 3 and Example 1 is:
[0119] In step (4), the heating temperature of the first heat treatment is 50°C, and the rest is the same as in Example 1.
[0120] Comparative Example 4
[0121] The difference between Comparative Example 4 and Example 1 is:
[0122] In step (4), the heating temperature of the first heat treatment is 130°C, and the rest is the same as in Example 1.
[0123] Comparative Example 5
[0124] The difference between Comparative Example 5 and Example 1 is:
[0125] In step (4), the heating time of the first heating treatment is 0.5 h, and the rest is the same as in Example 1.
[0126] Comparative Example 6
[0127] The difference between Comparative Example 6 and Example 1 is:
[0128] In step (4), the heating time of the first heating treatment is 15 hours, and the rest is the same as in Example 1.
[0129] Comparative Example 7
[0130] The difference between Comparative Example 7 and Example 1 is:
[0131] In step (5), the heating temperature of the second heat treatment is 30°C, and the rest is the same as in Example 1.
[0132] Comparative Example 8
[0133] The difference between Comparative Example 8 and Example 1 is:
[0134] In step (5), the heating temperature of the second heat treatment is 80°C, and the rest is the same as in Example 1.
[0135] Comparative Example 9
[0136] The difference between Comparative Example 9 and Example 1 is:
[0137] In step (5), the heating time of the second heating treatment is 4 hours, and the rest is the same as in Example 1.
[0138] Comparative Example 10
[0139] The difference between Comparative Example 10 and Example 1 is:
[0140] In step (5), the heating time of the second heating treatment is 30 hours, and the rest is the same as in Example 1.
[0141] Test Method
[0142] The electrochemical performance of the lithium ion batteries prepared in Examples 1 to 11 and Comparative Examples 1 to 10 was tested, and the specific method is as follows:
[0143] (1) Cycling performance: Full battery test of lithium-ion batteries at 25°C with constant current and constant voltage charging and discharging at a current density of 1C, with a charge and discharge voltage window of 3.0V-4.2V.
[0144] (2) Rate performance: The lithium-ion battery is charged at a current density of 1C and discharged at a current density of 3C with a constant current and constant voltage for full battery testing. The charge and discharge voltage window is 3.0V-4.2V.
[0145] The test results are shown in Table 1 below:
[0146]
[0147]
[0148] According to the test results in Table 1, the lithium ion battery provided in the embodiment adopts a two-step heating method for electrolyte thermal polymerization. Initiators such as benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate with higher activity can convert most of the polymer monomers in the electrolyte into solid polymers in a relatively short time during the first heating treatment, thereby reducing the side reactions between the polymer monomers and the electrodes at high temperatures and the problems of polymer aging and cracking; at the same time, initiators such as benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate themselves still have certain initiation activity at relatively low temperatures, which can promote the polymerization reaction of unreacted polymer monomers during the second heating treatment, further improve the conversion rate of polymer monomers, reduce the residual amount of polymer monomers and side reactions in the lithium ion battery, and effectively improve the cycle performance and rate performance of the lithium ion battery.
[0149] From the analysis of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that compared with only using the first heating treatment or only using the second heating treatment to carry out the thermal polymerization reaction of the polymer monomer, the present embodiment adopts a two-step heating method, which can improve the polymer monomer conversion rate while reducing side reactions and polymer aging and cracking, thereby improving the cycle performance and rate performance of the battery.
[0150] From the analysis of Example 1, Example 2, Example 3 and Comparative Example 3, Comparative Example 4, it can be known that setting the temperature of the first heat treatment in the range of 70°C-100°C can improve the expansion cracking of the polymer and the phenomenon of too fast polymerization reaction rate, increase the polymer monomer conversion rate, reduce the residual polymer monomer, and thus improve the mechanical properties and electrochemical properties of the battery.
[0151] From the analysis of Example 1, Example 4, Example 5 and Comparative Example 5, Comparative Example 6, it can be seen that setting the time of the first heat treatment in the range of 1h-12h can improve the polymer monomer conversion rate while reducing the side reactions between the polymer monomer and the electrode and the phenomenon of polymer aging and cracking, thereby improving the cycle performance and rate performance of the battery.
[0152] From the analysis of Example 1, Example 6, Example 7 and Comparative Example 7, Comparative Example 8, it can be seen that setting the temperature of the second heat treatment in the range of 45°C-60°C can further improve the polymer monomer conversion rate, reduce the occurrence of side reactions at high temperatures and the problem of polymer aging and cracking, thereby improving the cycle performance and rate performance of the battery.
[0153] From the analysis of Example 1, Example 8, Example 9 and Comparative Example 9, Comparative Example 10, it can be seen that setting the time of the second heat treatment in the range of 1h-12h can reduce the residue of polymer monomers and initiators, reduce battery impedance, and improve the rate performance of the battery.
[0154] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a lithium ion battery, characterized in that: The preparation method comprises the following steps: Providing an electrolyte, the electrolyte comprising a polymer monomer and an initiator, the initiator comprising at least one of benzoyl peroxide, N,N-dimethylaniline, and tert-butyl perbenzoate; Injecting the electrolyte into a battery cell, performing a first heating treatment on the battery cell to obtain an intermediate, wherein the heating temperature of the first heating treatment is 70° C.-100° C., and the heating time is 1 h-12 h; The intermediate is subjected to a second heating treatment to obtain the lithium-ion battery, wherein the heating temperature of the second heating treatment is 45° C.-60° C., and the heating time is 8 h-24 h.
2. The preparation method according to claim 1, characterized in that: The polymer monomer includes at least one of 2-phenoxyethyl acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, trifluoroethyl methacrylate, hexafluorobutyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, acrylonitrile, 2-cyano-3-ethoxyethyl acrylate, adiponitrile, hexamethylene diisocyanate, and vinyl trimethoxysilane; and / or The mass of the polymer monomer accounts for 0.1%-20% of the mass of the electrolyte; and / or The mass of the initiator accounts for 0.1%-2% of the mass of the electrolyte.
3. The preparation method according to claim 1 or 2, characterized in that: The preparation method of the electrolyte comprises the following steps: The polymer monomer, the initiator and other raw materials are mixed in a prescribed amount to obtain the electrolyte.
4. The preparation method according to claim 3, characterized in that: The other raw materials include organic solvents, lithium salts, additives and cross-linking agents; and / or The mixing is carried out in dry air, argon atmosphere or nitrogen atmosphere; and / or The mixing temperature is 20° C.-30° C., and / or the mixing time is 2 h-24 h.
5. The preparation method according to claim 4, characterized in that: The mass of the cross-linking agent accounts for 0.1%-10% of the mass of the electrolyte; and / or The mass of the organic solvent accounts for 70%-88% of the mass of the electrolyte; and / or The mass of the lithium salt accounts for 9%-20% of the mass of the electrolyte; and / or The mass of the additive accounts for 0.5%-10% of the mass of the electrolyte.
6. The preparation method according to claim 4, characterized in that: The cross-linking agent includes at least one of triethylene glycol dimethacrylate, diallyl disulfide, N,N-methylenebisacrylamide, propoxy neopentyl glycol diacrylate, pentaerythritol tetraacrylate, diallyl isophthalate, divinyl propylene terephthalate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, and divinylbenzene; and / or The organic solvent comprises at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate and propylene carbonate; and / or The lithium salt comprises at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluorooxalate phosphate, lithium bisfluorobisoxalate phosphate, lithium difluorophosphate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bisoxalate borate, and lithium difluorooxalate borate; and / or The additive includes at least one of vinylene carbonate, fluoroethylene carbonate, vinyl vinyl carbonate, 1,3-propane sultone, trimethylsilane, vinyl vinyl sulfite, and dimethyl sulfoxide.
7. The preparation method according to claim 1 or 2, characterized in that: Before the battery cell is subjected to the first heating treatment, a packaging step and a standing step are also included.
8. The preparation method according to claim 7, characterized in that: The packaging includes vacuum packaging, and the vacuum degree of the vacuum packaging is -70 kPa to -90 kPa.
9. The preparation method according to claim 7, characterized in that: The standing temperature is 20°C-30°C, and / or the standing time is 12h-48h.
10. A lithium ion battery, characterized in that: The lithium-ion battery is prepared by the preparation method according to any one of claims 1 to 9.